Efektivitas Pelaksanaan Program Simpan Dan Pinjam Perempuan (SPP) Terhadap Pendapatan Dan Kesempatan Kerja Di Kecamatan Kediri Kabupaten Tabanan - Adi Marantika, I Putu Agus; Rustariyani, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
Development in all sectors can be achieved if there is a role in establishing and implementing state policy in the field of public welfare (public welfare). Lack of capital is a factor of the low income and employment in poor households (RTM) to develop a small business owned. These problems led to the RTM can not increase the income and standard of living of the family. Research to identify the effective implementation of the SPP revolving on income and employment for RTM in the district of Kediri, Tabanan regency, for simple random sampling method using 93 respondents. The analysis tecnik method using statistic with t test. The analysis confirmed the effectiveness of the implementation of the SPP program revolving against income and employment is very effective, as well as positif significant to increase income and employment for RTM. Revolving SPP program needs to be given on an ongoing basis, and held coaching to RTM beneficiaries to increase income and employment opportunities as well as creativity in opening a new business.
Keywords: Revolving SPP , Revenue , Employment